P170 An evaluation of the effect of various barriers on the ability of elderly inpatients to use their inhaled medication. (December 2018) - Saeed, H; Wilkinson, S; Dewar, A
Abstract : Introduction: Respiratory conditions are very common amongst the older population with asthma and chronic obstructive pulmonary disease (COPD) potentially co-existing in more than 50% of elderly patients. 1 With inhaled therapy as the primary pharmacological management of both conditions, we aimed to evaluate inhaler competence amongst elderly inpatients and identify the impact of inhaler devices, cognitive function, inspiratory flow and specific comorbidities on inhaler technique, whilst also investigating patients' perceptions of their inhaled medication. Methods: Forty-four patients with COPD and asthma were recruited from a UK teaching hospital in November 2013. Patients were given an inhaler technique score (ITS) using a seven-step checklist which was then compared to potential barriers of inhaler use. The patient's inspiratory flow for their inhaler(s) was measured using the In-Check Dial. The inhalers covered were the metered dose inhaler (MDI) (±spacer devices) and dry powder inhalers (DPI) including the Accuhaler, Turbohaler and Handihaler. Associations were considered significant at p<0.05 for Mann-Whitney U tests. Results: Only 10 (23%) patients demonstrated at least one perfect ITS. A significantly lower ITS was found amongst MDIs compared to DPIs (p=0.032) and also in cognitively impaired patients (p=0.038). No significant difference in ITS was found between patients with at least one comorbidity and those with none (p=0.289). Twenty-eight (64%) patients were not inhaling within the clinically effective flow range for at least one of their inhalers. Twenty (80%) MDI users, a larger proportion than DPI users, rated their device easy to use and clinically beneficial. Conclusion: Many elderly inpatients demonstrated poor inhaler technique which could result in suboptimal management of their condition, leading to increased costs, doses and health implications. Inhaled therapy must be carefully selected after assessing individual patient characteristics such as cognitive impairment. Healthcare professionals must provide regular reviews of inhaler technique. It is recommended for a repeat study to be completed following the introduction of newer inhaler devices available to patients. References: Gibson PG, Simpson JL. The overlap syndrome of asthma and COPD: What are its features and how important is it?Thorax2009;64(8):728–35.